Selection and appointment of presidents of medical universities in Iran: Bridging reality and ideal through global and local evidence. - Leila Doshmangir; Mohammadhossein Somi; Sajad Lak; Neda Kabiri; Hossein Ebrahimipour; Omid Barati; Mohammadreza Amiresmaili; Mohammad Bazyar (PLoS ONE)
Background The selection of university presidents who oversee health systems within their respective provinces has become increasingly critical in Iran, subjecting to an ongoing scrutiny and debate. This study aims to clarify the selection process and identify the essential competencies required for appointing medical university presidents both in Iran and globally, while also proposing relevant policy recommendations. Methods This study employed a multi-method approach, incorporating a scoping review, document review, interviews, and brainstorming. The scoping review, conducted in September 2024, searching databases including PubMed, ISI Web of Knowledge, and Scopus. Interviews conducted from September 2024 to November 2024, were carried out with stakeholders from a diverse range, including university presidents, health ministers, healthcare managers, decision-makers, faculty members and key planners within the academic sector, whom were selected using purposive sampling method with maximum variation. A question guide was used, the main question of which included: essential characteristics and competencies of university president, prioritized criteria for decision making, feasibility of evidence-based decision-making, the process of selecting and appointing university presidents, and the strengths and weaknesses of this process. The data were analyzed using a framework analysis approach, informed by Modified Henry Mintzberg's Management Model and a model of policy competency. Documents related to the selection and appointment of medical university presidents, including rules, regulations, and circulars, were collected through a census approach using both manual and electronic methods. Relevant documents were systematically retrieved from the official websites of the involved organizations. Brainstorming conducted in December 2024 and was used to develop policy recommendations. Results Twenty six articles and 19 university protocols were included in the scoping review phase. Forty-two participants included in the qualitative phase of this study, most of who were president of a university. Also, 12 participants involved in the brainstorming phase. The responsibilities of a university president necessitating a blend of personal, interpersonal, professional and decisional competencies. In Iran, various factors including political preferences, lack of transparency and accountability, limited involvement from the university community, and insufficient emphasis on professional or technical competencies, influence the selection process of university presidents. The influence of some pressure groups including parliament representatives and the prevailing ideological climate within the Ministry of Health have varied across different governments, relegating essential professional competencies, such as the scientific credibility of the president, to low priority. Conclusions During various selection and appointment periods, political changes and pressure groups' interests have had a significant impact on the management changes in universities, and with governments' changes, managerial capabilities are overshadowed by political tendencies. This study's findings underscore the importance of transparency, evidence-based decision-making, and a systematic approach to the selection and appointment of presidents of medical universities. Implementing these insights can enhance the integrity of the selection process and improve governance in medical education in Iran.